Assignment of the structure of petrocortyne A by mixture syntheses of four candidate stereoisomers - Sui, Bin (2010)
Two different mixture synthesis routes have been used to make the four stereoisomers of petrocortyne A. A first quick and dirty route provided a mixture of the four isomers in non-selective fashion. Mosher and 2-naphthylmethoxyacetic acid (NMA) ester methods were developed to identify the components, and the mixture was partially resolved on analytical chiral HPLC to give the two pure enantiomers of petrocortyne A and the racemate of its diastereomer. A second fluorous mixture synthesis produced all four isomers of petrocortyne A in individual pure form. Comparison of spectra of Mosher derivatives of the synthetic isomers with two supposedly different natural products showed that both natural samples were instead identical and had the (3S,14S) configuration. Likewise, petrocortynes B, D and F–H are (3S,14S) and petrocortyne D is (3R,14S). Having access to all possible candidate isomers of both petrocortyne A and its Mosher derivatives provided a secure structure assignment not so much because one of the isomers matched the natural product, but because all of the other isomers did not.